PERAN KEPRIBADIAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Siregar, Alfi Syahrah; Utama, Dian Herdiana (IKIP Siliwangi, 2024)
This study examines the effect of teacher personality competence on student learning motivation in Aqidah Akhlak at Madrasah Ibtidaiyah Negeri (MIN) 2 Padangsidimpuan. The proposed hypothesis states that teachers' attributes and behaviours significantly affect students' motivation, which in turn affects the effectiveness of the learning process. This research uses a quantitative descriptive approach by collecting data through questionnaires and documentation from 28 student respondents. Data analysis was conducted using the Product Moment formula. The results showed a correlation coefficient rcount of 0.538, which exceeds the rtable value of 0.374 at the 5% significance level. This supports the hypothesis that teacher personality competence positively affects student learning motivation. The findings emphasise the critical role of teacher personality in shaping educational outcomes and recommend the importance of professional development programs aimed at improving teachers' personality competence with positive and constructive behaviours in teaching and presenting themselves as an ideal figure that students respect and love.